Dampak Stunting Terhadap Kecerdasan Anak Dalam Perspektif Islam - Abu Khurairoh; Hermawan (Penerbit Minhaj Pustaka, 2025)
Stunting is a condition of impaired growth in children caused by chronic malnutrition, recurrent infections, and inadequate stimulation. This issue not only affects a child's physical development but also hinders their cognitive and intellectual growth, ultimately impacting their future quality of life and productivity. From an Islamic perspective, safeguarding children's health and intelligence is a parental and societal responsibility, aligned with the principles of Maqasid al-Sharia, particularly the preservation of progeny (hifzh al-nasl) and intellect (hifzh al-'aql). This article examines the effects of stunting on children's intellectual development and proposes preventive solutions based on Islamic teachings. These solutions include ensuring proper nutrition from pregnancy, exclusive breastfeeding, parenting practices guided by religious principles, and community support in preventing stunting. The Islamic approach to addressing stunting emphasizes the balance between physical, spiritual, and social aspects, enabling children to thrive holistically. Therefore, stunting prevention is not just an individual duty but also a collective responsibility in nurturing a healthy, intelligent, and morally upright generation in accordance with Islamic values. Abstrak Stunting adalah kondisi gagal tumbuh pada anak yang disebabkan oleh kekurangan gizi kronis, infeksi berulang, dan stimulasi yang tidak memadai. Masalah ini tidak hanya berdampak pada pertumbuhan fisik anak tetapi juga menghambat perkembangan kognitif dan kecerdasannya, yang pada akhirnya dapat memengaruhi kualitas hidup dan produktivitasnya di masa depan. Dalam perspektif Islam, menjaga kesehatan dan kecerdasan anak merupakan tanggung jawab orang tua dan masyarakat selaras dengan prinsip Maqashid Syariah, khususnya dalam menjaga keturunan (hifzh al-nasl) dan akal (hifzh al-'aql). Artikel ini mengkaji dampak stunting terhadap perkembangan intelektual anak serta menawarkan solusi pencegahan berbasis nilai-nilai Islam. Solusi tersebut mencakup pemenuhan gizi yang baik sejak masa kehamilan, pemberian ASI eksklusif, pola asuh yang sesuai dengan tuntunan agama, serta peran komunitas dalam mendukung keluarga untuk mencegah stunting. Pendekatan Islami dalam penanganan stunting menekankan pentingnya keseimbangan antara aspek fisik, spiritual, dan sosial, sehingga anak dapat tumbuh optimal secara jasmani dan rohani. Dengan demikian, upaya pencegahan stunting tidak hanya menjadi tanggung jawab individu, tetapi juga bagian dari amanah kolektif dalam mewujudkan generasi yang sehat, cerdas, dan berkualitas sesuai dengan nilai-nilai Islam.